A national survey of radiation oncologists and urologists on recommendations of prostate‐specific antigen screening for prostate cancer. (17th January 2014) - Kim, Simon P.; Karnes, R. Jeffrey; Nguyen, Paul L.; Ziegenfuss, Jeanette Y.; Thompson, R. Houston; Han, Leona C.; Shah, Nilay D.; Smaldone, Marc C.; Gross, Cary P.; Frank, Igor; Weight, Christopher J.; Beebe, Timothy J.; et al.
Abstract : Objective: To assess recommendations for prostate‐specific antigen (PSA) screening in a national survey of radiation oncologists and urologists following the recent USA Preventive Services Task Force (USPSTF) grade D recommendation. Methods: A random sample of 1366 radiation oncologists and urologists were identified from the American Medical Association Physician Masterfile. From November 2011 to April 2012, a mail survey was sent to query PSA screening recommendations for men at average risk of prostate cancer for the following age groups: 40–49, 50–59, 60–69, 70–74, 75–79 and ≥80 years. Multivariable logistic regression was used to test for differences in PSA‐based screening recommendations by physician characteristics. Results: Response rates were similar at 52% for radiation oncologists and urologists ( P = 0.92). Overall, 51.5% of respondents recommended PSA‐based screening for men aged 40–49 years, while nearly all endorsed it for those aged 50–74 years (96.1% for 50–59, 97.3% for 60–69, and 87.7% for 70–74 years). However, screening recommendations decreased to 43.9% and 12.8% for men aged 75–79 and ≥80 years, respectively. On multivariable analysis, urologists were more likely to recommend screening for men aged 40–49 (odds ratio [OR] 3.09; P < 0.001) and 50–59 years (OR 3.81; P = 0.01), but less likely for men aged 75–79 (OR 0.66; P = 0.01) and ≥80 years (OR 0.45; P = 0.002) compared with radiation oncologists. Conclusion: While radiation oncologists and urologists recommended PSA screening for men aged 50–69 years, there was less agreement about screening for younger (40–49 years old) and older (≥70 years) men at average risk for prostate cancer.